Development of Nifedipine Phytantriol-Based Cubosomes and In Vitro Simulation of Administration Through Pediatric Feeding Tubes - Lorena Almeida Lima; Euler Eduardo Lisboa de Moura; Schauana Freitas Fraga; Renata Vidor Contri; Irene Clemes Külkamp-Guerreiro (Pharmaceutics)
Background/Objectives: This study focused on developing an organic solvent-free formulation of phytantriol-based cubosomes for nifedipine delivery. It assessed the physicochemical properties and in vitro administration performance in pediatric nasogastric tubes and preliminarily evaluated toxicity in a brine shrimp lethality model. Methods: The nanocarrier formulation was characterized in terms of the particle size and drug release properties and was compared with extemporaneous formulations prepared using nifedipine tablets in flow rate tests through pediatric feeding tubes. The recovery efficiency was evaluated across different tube sizes and rinsing volumes. A preliminary toxicity study was conducted using a brine shrimp lethality model. Results: Compared with nifedipine tablets, the nanocarrier formulation demonstrated favorable physicochemical properties, including controlled release and superior flow rates, in the pediatric tubes. Full recovery of the nifedipine content was achieved with the nanocarrier formulation, whereas extemporaneous formulation of the nifedipine recovery depended on the tube dimensions and rinsing protocols. Conclusions: Compared with the traditional formulations, the nanocarrier formulation represents a promising alternative for administering nifedipine via pediatric feeding tubes, offering an enhanced administration recovery.